STOCK-BOND RETURN CORRELATION IN THE PAST 25 YEARS: Empirical Evidence from the US, the UK, Germany and Japan - Wang, Cong (My University, 2017)
Stocks and bonds are two major asset classes in the financial market. Understanding the comovement between stock and bond returns are of great importance in portfolio selection, asset allocation and risk management. This thesis examines the comovement between MSCI stock index returns and 10-year benchmark government bond index returns in the US, the UK, Germany and Japan over the period from January 1992 to December 2016. Three approaches are employed to calculate the time-varying correlation coefficients: the realized correlation, the asymmetric dynamic conditional correlation, and wavelet analysis. Different approaches give qualitatively consistent results. The influence of macroeconomic factors such as the inflation rates, the industrial production rates, and the short-term interest rates as well as the global market uncertainty, on the stock-bond correlation, is investigated through a regression approach. The major findings are as follows. Stock-bond correlations are rather unstable and vary significantly over the last 25 years. The US, the UK, and Germany show a similar pattern of stock-bond comovement, whereas Japan seems to be segmented from the global market. Among all factors under investigation, the CBOE volatility index – VIX, plays the most significant role in the stock-bond comovement. VIX has a clearly negative impact on the stock-bond correlation. The short-term interest rates are found to be positively related to the stock-bond correlation. This study does not find clear evidence to show that inflation rates or industrial production rates have a systematic linkage with the stock-bond correlation. Finally, monthly macroeconomic factors are not able to well explain the long time horizon variations in the stock-bond correlation.
Keywords: stock-bond correlation; realized correlation; ADCC; wavelet analysis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|